2003
DOI: 10.1039/b209759c
|View full text |Cite
|
Sign up to set email alerts
|

Diazacoronand linked β-cyclodextrin dimer complexes of Brilliant Yellow tetraanion and their sodium(I) analoguesβ-Cyclodextrin = cyclomaltoheptaoseElectronic supplementary information (ESI) available: Molar absorbance and 2D NMR ROESY spectra of 1 and 2, and their complexes with 34–. See http://www.rsc.org/suppdata/ob/b2/b209759c/.

Abstract: Complexation of the Brilliant Yellow tetraanion, 3(4-), by two new diazacoronand linked beta-cyclodextrin (beta CD) dimers 4,13-bis(2-(6A-deoxy-beta-cyclodextrin-6A-yl)aminooctylamidomethyl- and 4,13-bis(8-(6A-deoxy-beta-cyclodextrin-6A-yl)aminooctylamidomethyl)-4,13- diaza-1,7,10-trioxacyclopentadecane, 1 and 2, respectively, has been studied in aqueous solution. UV-visible spectrophotometric studies at 298.2 K, pH 10.0 and I = 0.10 mol dm-3 (NEt4ClO4) yielded complexation constants for the complexes 1 x 3(4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 25 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…Secondary interactions between tether and guest molecule may lead to higher binding affinities and consequently give rise to relatively high EM values. A clear example is entry 6 of Table 2, in which ligation of the phosphate moiety of the guest molecule to the metal ion complexed at the tether resulted in an EM of 1.0 M. Similar effects have been observed for other metal-chelated cyclodextrin dimers and charged guest molecules, 76 and for intramolecular chelation of the tether to metal-containing guest molecules. 77 In most cases, however, the effective molarities are probable effective concentrations, indicating that guest molecules are generally bound in a noncooperative, statistical fashion.…”
Section: Cyclodextrin Host-guest Complexessupporting
confidence: 59%
“…Secondary interactions between tether and guest molecule may lead to higher binding affinities and consequently give rise to relatively high EM values. A clear example is entry 6 of Table 2, in which ligation of the phosphate moiety of the guest molecule to the metal ion complexed at the tether resulted in an EM of 1.0 M. Similar effects have been observed for other metal-chelated cyclodextrin dimers and charged guest molecules, 76 and for intramolecular chelation of the tether to metal-containing guest molecules. 77 In most cases, however, the effective molarities are probable effective concentrations, indicating that guest molecules are generally bound in a noncooperative, statistical fashion.…”
Section: Cyclodextrin Host-guest Complexessupporting
confidence: 59%
“…Binding Stoichiometry. Several stoichiometric ratios between CDs and guests, such as 1:2, 2:1, and 2:2, have been reported, , but the most common ratio has hitherto shown to be 1:1. The stoichiometric ratios ( N value) that we observed from the binding patterns for the titrations of steroids with bridged bis( β -CD)s 2 − 7 fell within the range of ∼1.8−2.1:1.…”
Section: Resultsmentioning
confidence: 99%
“…Bridged bis( β -cyclodextrin(CD))s, as a very important family of CD derivatives, have been known to alter significantly the molecular binding ability and selectivity toward a variety of guests in comparison with parent β -CDs through the cooperative binding of a single model substrate by two hydrophobic cavities located in a closely vicinity and therefore provide an excellent model system mimicking the substrate-specific interaction of enzymes On the other hand, the inclusion complexation of bridged bis( β -CD)s toward guest molecules does not always give the cooperative 1:1 binding of a single guest molecule by the two hydrophobic cavities located in close vicinity. Our recent investigation results demonstrated that a paclitaxel and a bridged bis( β -CD) containing an appropriate spacer could form a 1:2 inclusion complex through the binding of each cavity of the bis( β -CD) with one paclitaxel molecule, and this noncooperative binding mode had been successfully applied onto the solubilization increase of paclitaxel .…”
Section: Introductionmentioning
confidence: 99%
“…Investigations on the inclusion complexation of native and modified cyclodextrins (CDs) have received much attention in supramolecular chemistry and become the fundamental basis of molecular assembly. In the inclusion complexation process, besides several weak intermolecular noncovalent forces, such as dipole−dipole (ion), hydrophobic, electrostatic, van der Waals, and hydrogen bonding interactions, the solvent, environment, and conformations of hosts and guests will also affect the stability of host−guest complexes. The strong binding affinity of CDs to hydrophobic molecules in aqueous media enables them to be effective receptors for organic, inorganic, and biological substrates. Furthermore, lots of chemically modified CDs have been designed and synthesized to enhance the original binding ability and the molecular selectivity of parent CD. As one of the most important categories, CD derivatives bearing a chromophoric substituent, such as an azo group, can exhibit the appreciable spectral changes upon inclusion complexation with guests, and thus be successfully applied as the versatile spectral probe to investigate the host−guest complexation. As a method to control the stability, solubility, and aggregation of azo dyes, their inclusion complexation with CDs has been widely investigated. Recently, Ueno et al reported several azo dyes modified β -CDs as guest responsive color-change indicators .…”
Section: Introductionmentioning
confidence: 99%